PRIMACY OF LANGUAGE DOMAINS PERTAINING TO TENYIDIE LANGUAGE PROFICIENCY - Sorhie, Petekhrienuo; Sachu, Nokesel (International Journal of Research -GRANTHAALAYAH, 2024)
Human beings are a social animal and we progress through communication by using language. Effective communication is needed in our day to day lives and in order to communicate effectively it is significant to attain the language domain effectively as well. Language domain is a communication skill, it is the ability to listen, speak, read and write. The improvement of the four language domains can enable an individual to develop proficiency in Tenyidie. The effective communication depends on the level of how well an individual can use a language accurately and aptly. One cannot become proficient or master a language by overnight rather it is through practice and proper learning of language skills one can attain the desired proficiency in Tenyidie language. This paper aims to discuss the primacy and importance of the language domains and bring out suggestive measures towards improving language skills straddled with the intent to motivate learners to acquire proficiency in Tenyidie language.